SELF-EFFICACY DENGAN FEAR OF MISSING OUT (FOMO) PADA REMAJA - Glenn Joan Halim; Monika (STKIP Subang, 2024)
This study aims to examine the relationship between self-efficacy and Fear of Missing Out (FoMO) in high school students. Self-efficacy is an individual's belief in their ability to manage and complete tasks, while FoMO is anxiety that arises due to feeling left behind from social experiences that are considered important. This study used a quantitative correlational approach, with 213 high school students as participants. Data collection was carried out using the Self-Efficacy Questionnaire for Children (SEQ-C) scale and the standardized Fear of Missing Out Scale (FoMOs). The results of data analysis using the Spearman correlation method showed a significant negative relationship between self-efficacy and FoMO (r = -0.254, and p = 0.000 <0.05). These findings indicate that students with high levels of self-efficacy tend to have lower levels of FoMO.